2009
DOI: 10.1371/journal.pone.0006514
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Ras Signaling Pathway to Direct Selective Replication of Herpes Simplex Virus-1

Abstract: Re-engineering the tropism of viruses is an attractive translational strategy for targeting cancer cells. The Ras signal transduction pathway is a central hub for a variety of pro-oncogenic events with a fundamental role in normal and neoplastic physiology. In this work we were interested in linking Ras activation to HSV-1 replication in a direct manner in order to generate a novel oncolytic herpes virus which can target cancer cells. To establish such link, we developed a mutant HSV-1 in which the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Oncolytic virus therapy is based on the ability of viruses to effectively infect and kill tumor cells without harming the normal tissues. While some viruses seem to have a natural preference for tumor cells, most viruses require the modification in their tropism to specifically enter and/or replicate in cancer cells . Permissiveness of cells to reovirus (a RNA oncolytic virus currently in advanced clinical trials ) has been shown to be dependent on RalA signaling .…”
Section: Oncolytic Viruses and Ral Signalingmentioning
confidence: 99%
“…Oncolytic virus therapy is based on the ability of viruses to effectively infect and kill tumor cells without harming the normal tissues. While some viruses seem to have a natural preference for tumor cells, most viruses require the modification in their tropism to specifically enter and/or replicate in cancer cells . Permissiveness of cells to reovirus (a RNA oncolytic virus currently in advanced clinical trials ) has been shown to be dependent on RalA signaling .…”
Section: Oncolytic Viruses and Ral Signalingmentioning
confidence: 99%
“…Intended functions range from activating chemotherapy prodrugs (3843), to augmenting host immune response to tumor cells (4449), to inducing anti-angiogenesis proteins (5054). Still other vectors have been constructed with tumor-specific promoters, designed to respond either to certain elements of a microenvironment, like hypoxia (typical of tumor cells), or to an antigen or protein expressed predominantly by cancer cells (16;5558). The progress of these armed vectors marks a promising future for targeted oncolytic virotherapies.…”
Section: Evolution Of Oncolytic Herpes Simplex Virusmentioning
confidence: 99%
“…In recently published literature, gene silencing by RNA interference technology to achieve tumor selectivity has also been utilized (145). Furthermore; another strategy used is to involve the insertion of a tumorspecific promoter (148,149), by doing this the expression of a gene necessary for viral replication in order to restrict its replication in tumor cells is overexpressed (145). TOVs can also be engineered to express cell surface receptors unique to tumor cells (150,151), which allow specific tropism (145).…”
Section: Oncolytic Virotherapymentioning
confidence: 99%